The resilience of foreign remittances in the time of pandemic: Bangladesh perspective - Rahman, Moshiur Mohammad; Haque, A. K. M. Ahasanul; Suib, Fatin Husna (MAC Arts & Communication, 2021)
Foreign remittances have contributed significantly to Bangladesh’s overall economic development through the years. More than half a million Bangladeshi citizens work abroad, which lessens the country’s labour market burden. As a result, Bangladesh is deemed a big beneficiary of remittances, earning USD 21.8 billion in 2020. It is inseparably linked to economic matters and influenced Bangladesh’s economic strengths. However, it endured appallingly during the recent worldwide COVID-19 outbreak and has already seen remittance inflows fall. This article examines the effects of foreign remittances on the COVID-19 issue and the link between remittances and the general stability of Bangladesh’s economy. Also, suggested some possible courses of action to face these challenges in an effective way. The recommendations derived from this study findings will aid to increase the valuable remittances and overall welfare for the society.